Active methodology in nursing education: innovation of the practice in the primary health care - Patrícia Madalena Vieira Hermida; Sarah Soares Barbosa; Ivonete Teresinha Schülter Buss Heidemann (Universidade Federal de Santa Maria, 2015)
Aim: to report the experience of applying an active methodology of teaching and learning with nursing students in primary health care. Method: experience report. Eight students and one teacher participated, in a morning of practical activity of a health unity in Florianopolis, Santa Catarina, Brazil. The methodology was applied in eight distinct, sequential and complementary phases. Results: the students were initially stimulated to represent a situation of health/disease and seek support at the Health Centre as users, posteriorly they observed the facility structure and socialized the individual experiences. During the whole process, the students were stimulated to reflect and share their experiences, to discuss the functioning of the service and the professionals' roles. Final Considerations: it was an important experience in different ways of teaching and learning that involved both teachers and students